Quality Strategy and its role in Improving the Performance of Charitable Sector Establishments - A case study in the Aseer Region Branch - Al Mashari, Abdullah Hassan Abdullah; Al Qadan, Abdulaziz Saleh Saad; Al Ghasham, Nayef Abdulwahab Saeed (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of the research is to identify the comprehensive quality strategy and its role in improving the performance of the charitable sector establishments, as the descriptive analytical approach was used, the research tool was a questionnaire; It was distributed to a simple random sample of (297) workers in charitable sector facilities in the Asir region in the Kingdom of Saudi Arabia. the research reached several results, the most important of which is that the dimensions of the comprehensive quality strategy (focus on the beneficiary, leadership commitment to quality, employee participation) are being applied at a high degree, and as a percentage (83.52%, 81.48%, 81%) for the three dimensions, respectively, and the results indicated that the level of improvement in the performance of workers in the charitable sector facilities in the Asir region came To a large degree, In percentage (73.73%), there is also a statistically significant relationship between the dimensions of total quality management (focus on the beneficiary, leadership commitment to quality, employee participation) and improving the performance of charitable sector establishments in the Asir region, and in light of the results, the researchers recommend the necessity for charitable sector establishments to follow up on complaints by submitting complaints. Flexibility to deal with complaints submitted by auditors and work to solve them, as well as the commitment of the facilities management operating in the charitable sector to flexibility in the organizational structure to suit With the requirements of quality, which contributes to expanding the scope of supervision and work according to empowerment and administrative authorization, and finally the research recommends solving the problems of employees working in the facilities of the charitable sector and activating their role.